MAKNA DAN TRADISI-TRADISI DALAM RANGKAIAN TRADISI KHATAM QURAN ANAK-ANAK DI NAGARI BALAI GURAH SUMATERA BARAT - Wirdanengsih, Wirdanengsih (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2019)
This article tries to reveal the analysis of cultural and educational value on the traditions of Khatam Quran children at village Balai Gurah Agam district of West Sumatra. In addition this paper also reveals the meaning of the tradition for the Balai Gurah community . The observation, in-depth interviews and the review of date secondary.. The results of this study found that the tradition of Khatam Quran in villages of Balai Gurah is one of the traditions that express the religious culture of Minangkabau society. For the people of Balai Gurah, tradition Khatam Quran is an initiation process in children and a form of gratitude for the intelligence of children in reading the Quran. Tradition Khatam Quran also has significance awareness in social relationships between people, especially in building unity and mutual assistance among relatives and the community. Tradition Khatam Quran also have the meaning of economic, religius and socio-cultural for the community, In A series of Khatam Quran ceremony is gathered some traditions such as the tradition of musyawarah mufakaik , traditin of makan bajamba , tradition of Mandabiah Jawi, tradition of Talempong music , the tradition of arak-arakan and tradition manyumbang. All that has the meanings.